DESENVOLVIMENTO IN SILICO DE MOLÉCULAS ANÁLOGAS AO DIAZEPAM E ESTUDO COMPARATIVO DOS PARÂMETROS FARMACOLÓGICOS E TOXICOLÓGICOS (REMUNOM, 2025)
Benzodiazepines are believed to be among the most used classes of drugs in the world, Diazepam is part of this class of drugs which is responsible for treating symptoms of anxiety, agitation and insomnia in a large part of the population. In this context, the present study aimed to make modifications in the Diazepam molecule to obtain analogous molecules with a better pharmacological and toxicological profile, in order to expand the therapeutic arsenal for the treatment of anxiety. Thus, the molecules were designed using the ACD/ChemSketch software, where the molecular modifications were also made, and the molecules were saved, optimized and exported in 3D format and imported to the Swiss target Prediction, PreADMET and ProTox-3 analysis platforms. Analogous molecules have a higher than 50% probability of binding, but lower than Diazepam. It was also evidenced that the analogous molecules showed a small decrease in the ability to cross the blood-brain barrier, presented a medium risk of causing arrhythmia, were not mutagenic in the TA1535 strains (except the molecules ACl, AC and AF), while among the metabolites of all substances none showed mutagenicity changes, however in the TA100 strains all molecules showed mutagenicity. Most analogues had a higher lethal dose than Diazepam, giving a higher safety margin than Diazepam. It was noted that most of the molecules derived from Diazepam had a good pharmacological and toxicological profile, and the ACL2 molecule was the analogue with the best profile.